Biology of black scabbardfish (Aphanopus carbo Lowe, 1839) and standardization of commercial LPUE data of Aphanopus spp. landed in Madeira Archipelago, Portugal - Gomes, César Paulo Vieira (2017)
Dissertação de mestrado, Biologia Marinha, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2016